Regulatory lessons from China’s COVID-19 vaccines development and approval policies - Jingshu Yang; Yue Yang (Acta Materia Medica, 2022)
Coronavirus disease 2019, responsible for a global pandemic, is caused by the severe acute respiratory syndrome coronavirus 2. Several vaccines have been developed and approved worldwide, particularly in China. As of Oct 17, 2021, four new coronavirus vaccines in China have been conditionally approved for marketing by the National Medical Products Administration, two of which have been authorized for emergency use in the Emergency Use Listing of the World Health Organization. Domestic vaccine R&D in China has relied on legal and regulatory support. This article summarizes the regulatory policy for vaccine development, review and approval. Vaccine approval laws have been continually improved, and regulations for special approval have been used to shorten the review time. China has coordinated pandemic-related needs, both domestically and with other countries, and made substantial progress in cooperative international anti-pandemic efforts.